2007
DOI: 10.1016/j.virusres.2006.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The tyrosine kinase inhibitor genistein blocks HIV-1 infection in primary human macrophages

Abstract: Binding of HIV-1 envelope glycoprotein (Env) to its cellular receptors elicits a variety of signaling events, including the activation of select tyrosine kinases. To evaluate the potential role of such signaling, we examined the effects of the tyrosine kinase inhibitor, genistein, on HIV-1 entry and infection of human macrophages using a variety of assays. Without altering cell viability, cell surface expression of CD4 and CCR5 or their abilities to interact with Env, genistein inhibited infection of macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 107 publications
3
50
0
Order By: Relevance
“…Another study reported a block of entry and postentry events with the B oligomer of PTX, which modulates signaling independent of G␣ i . Additional studies reported that the tyrosine kinase inhibitor genistein blocks HIV-1 infection in primary human macrophages and that RhoA and filamin A are required for the actin-dependent clustering of CD4 and coreceptor required for membrane fusion (1,20,31,54). These findings indicate that HIV-1 Env-induced signaling plays a crucial role in Env-mediated membrane fusion.…”
Section: Discussionmentioning
confidence: 90%
“…Another study reported a block of entry and postentry events with the B oligomer of PTX, which modulates signaling independent of G␣ i . Additional studies reported that the tyrosine kinase inhibitor genistein blocks HIV-1 infection in primary human macrophages and that RhoA and filamin A are required for the actin-dependent clustering of CD4 and coreceptor required for membrane fusion (1,20,31,54). These findings indicate that HIV-1 Env-induced signaling plays a crucial role in Env-mediated membrane fusion.…”
Section: Discussionmentioning
confidence: 90%
“…[26][27][28][29][30][31][32][33][34][35] Multiple screens for HIV-1 inhibitors relied on in vitro assays, which used viral proteins or their fragments, or on HIV-1 infections/replication as a readout. In vitro screening has identified competitive inhibitors of assembly of the gp41 HR1-and HR2-derived peptides into the 6HB.…”
Section: Introductionmentioning
confidence: 99%
“…Host signaling through RTKs and other tyrosine kinases has also been shown to play important roles in virus replication. The tyrosine kinase inhibitor genistein was found to block replication of HIV-1, herpes simplex virus type 1 (HSV-1), and arenavirus (51,53,61), for example, and Src family kinases are known to be important for assembly and maturation of dengue virus and West Nile virus (6,19). The Raf/MEK/ERK (42) and PI3K/Akt (9, 10, 15) pathways downstream of RTKs play important roles in influenza virus replication.…”
mentioning
confidence: 99%